Resíduos eletroeletrônicos e práticas de educação ambiental crítica na formação do sujeito crítico - Nascimento, Rosane Rosário do (2023)
This research aimed to develop actions that show the processes surrounding the consumption and adequate disposal of electronic waste at the Colégio Estadual Professor João de Oliveira in the municipality of Poço Verde, SE, through critical Environmental Education practices that promote the formation of the subject critical. The relationship between productivity and consumption, especially in the young population, increases the production of electronic waste and its inadequate disposal in the environment, generating significant socio-environmental impacts, being a subject little discussed in the school context. For theoretical deepening, the study spoke with some authors about some points that corroborate the understanding of the problem situation. It is characterized by bibliographical and intervention research, addressing Freiriana dialectics. Data collection has a qualitative approach, using the diary and field guide as collection instruments. The application of field research with young people in the 2nd year of high school, through techniques and methodological resources that were organized in the classroom, with the practice of interdisciplinary, playful and interpretative activities, which made it possible to work with the critical opinion of the participants. The study showed that the approach through Critical Environmental Education practices helps in the formation of the critical subject and, in this way, reduces the demand that drives increased productivity and allows discussing the reduction of waste generation and correct forms of disposal. From the application of the intervention and availability of information to students, it was found that young people, despite being at the center of consumption, are open and directly concerned with environmental causes.